Dispersed emergence and protracted domestication of polyploid wheat uncovered by mosaic ancestral haploblock inference - Zihao Wang; Wenxi Wang; Xiaoming Xie; Yongfa Wang; Zhengzhao Yang; Huiru Peng; Mingming Xin; Yingyin Yao; Zhaorong Hu; Jie Liu; Zhenqi Su; Chaojie Xie; et al. (Nature Communications, 2022)
The contribution of ancient haplotypes to domestication is largely unknown. Here, the authors develop an ancestral genomic haploblock dissection method to generate a mosaic pan-ancestry genomic map and reveal that the domesticated polyploidy wheat emerged from the admixture of six founder wild emmer linages.